Media for growth and yield of calla lily (Zantedeschia elliotiana) in Andaman and Nicobar Islands - BASKARAN, V; ABIRAMI, K; VELMURUGAN, A; SINGH, D R (The Indian Journal of Agricultural Sciences, 2019)
Calla lily (Zantedeschia elliottiana W. Wats.) is an attractive cut flower and a popular pot plant in commercial floriculture industry. This is an introduced crop in Andaman and Nicobar Islands and the use of growing media as substrate showed potential influence on growth and yield of cut flowers when compared to soil media. The growing media containing soil: sand: coir compost: vermicompost @2:1:1:1 recorded early sprouting (18.6 days), maximum number of shoots per plant (3.93), maximum number of leaves per plant (8.35), maximum stalk length (52.02 cm), flower diameter (16.0 cm), flower duration (15.5 days), number of flowers per plant (4.32), early flowering (72.02 days), maximum number of tubers per plant (3.27), maximum tuber weight (130.5 g) and maximum size of tuber (14.25 cm). Thus for commercial cultivation of calla lily the use of substrate media containing soil: sand: coir compost: vermicompost @2:1:1:1 (T5) was the best over soil for better vegetative, flowering and tuber growth.